Politics of the Mandate of Heaven: Metaphysics in Practice (Journal of humanities and social sciences exploratio, 2025)
This paper aims to respond to the foundational crisis faced by contemporary philosophy (understood as the ontology grasped by modern individuals) by proposing an onto-praxis metaphysical framework grounded in confronting death: the "Politics of the Mandate of Heaven." It begins by critiquing the inauthenticity of "Dasein's death" in Heidegger's ontology, arguing that his poetic ontology of "Ereignis" evades the reality of death, resulting in an empty existentialism devoid of genuine practice. Subsequently, in the pursuit of practice, the paper emphasizes the importance of a relational ontology for human existence, defining the human being (Dasein) as an "I" coexisting with the "Other." It clarifies that the individual must confront the existential horizon of nothingness and contingency and engage in an ontological life-projection upon it. Finally, the paper fully unfolds the theme of the "Politics of the Mandate of Heaven," revealing it as a form of metaphysical praxis. Within this framework, Dasein, amidst its historicity and alienation, returns to its authentic self and fulfills its mandate through practice, elucidating a fundamental harmony and co-actualization between the individual and the community at the ontological level. The entire text attempts to reconstruct, within the radical abyssal groundlessness, a philosophical possibility that faces Being itself, courageously confronts death, and assumes historical destiny.
Keywords: Ontology; Ontology-Practice; Political Mandate of Heaven; Metaphysics